PENGARUH HARGA TERJANGKAU DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MAHASISWA PADA ANOMALI HAIRCUT - Rahma Adila, Asyifa (DINAMIKA (Jurnal Manajemen Akutansi Bisnis dan Kewirausahaan), 2025)
This study aims to analyze the influence of affordable pricing and service quality on customer loyalty among university students at Anomali Haircut in Bandar Lampung. Students, as consumers, have unique characteristics such as limited financial resources, making price a crucial factor in purchase decision-making, while service quality also plays a vital role in customer satisfaction and attachment. Using a descriptive qualitative approach, data were collected through in-depth interviews with several informants who are loyal student customers. The findings reveal that competitive and affordable prices, along with friendly, fast, and high-quality service, significantly foster customer trust and emotional attachment to the barbershop services, ultimately strengthening customer loyalty. These findings are expected to offer practical insights for barbershop entrepreneurs in designing pricing strategies and improving service quality, as well as theoretical contributions to the development of service marketing, particularly in understanding the consumer behavior of university students.